Anatomy of Inferior Mesenteric Artery in Fetuses. (22nd May 2016) - Nuzhat, Ayesha
Abstract : Aim . To analyze Inferior Mesenteric Artery in fetuses through its site of origin, length, diameter, and variation of its branches. Method . 100 fetuses were collected from various hospitals in Warangal at Kakatiya Medical College in Andhra Pradesh, India, and were divided into two groups, group I (second-trimester fetuses) and group II (third-trimester fetuses), followed by dissection. Result . (1) Site of Origin . In group I fetuses, origin of Inferior Mesenteric Artery was at third lumbar vertebra in 33 out of 34 fetuses (97.2%). In one fetus it was at first lumbar vertebra, 2.8%. In all group II fetuses, origin of Inferior Mesenteric Artery was at third lumbar vertebra. (2) Length . In group I fetuses it ranged between 18 and 30 mm, average being 24 mm except in one fetus where it was 48 mm. In group II fetuses the length ranged from 30 to 34 mm, average being 32 mm. (3) Diameter . In group I fetuses it ranged from 0.5 to 1 mm, and in group II fetuses it ranged from 1 to 2 mm, average being 1.5 mm. (4) Branches . Out of 34 fetuses of group I, 4 fetuses showed variation. In one fetus left colic artery was arising from abdominal aorta, 2.9%. In 3 fetuses, Inferior Mesenteric Artery was giving a branch to left kidney, 8.8%. Out of 66 fetuses in group II, 64 had normal branching. In one fetus left renal artery was arising from Inferior Mesenteric Artery, 1.5%, and in another fetus one accessory renal artery was arising from Inferior Mesenteric Artery and entering the lower pole of left kidney. Conclusion . Formation, course, and branching pattern of an artery depend on development and origin of organs to attain the actual adult position.